2018
DOI: 10.4209/aaqr.2017.05.0156
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Chemical Mechanisms in the WRF-Chem Model in Reconstructing Aerosol Concentrations and Optical Properties in the Tibetan Plateau

Abstract: To investigate the effect of gas-phase chemical schemes and aerosol mechanisms on the reconstruction of the concentrations and optical properties of aerosols in the Tibetan Plateau (TP) and adjacent regions, two simulation experiments using the mesoscale Weather Research and Forecasting (WRF) meteorological model with the chemistry module (WRF-Chem) were performed in 2013. The RADM2 gas-phase chemical mechanism and the MADE/SORGAM aerosol scheme were selected in the first configuration, whereas the CBMZ gas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…As one of the major components of primary aerosols, sea-salt aerosols contributes to 20 %-40 % of secondary inorganic aerosols (SIAs) over coastal regions Yang et al, 2016). These particles can provide surface areas for condensation and reaction of nitrogen and sulfur, making the simulated concentrations of SIAs more accurate (Kelly et al, 2010;Im, 2013).…”
Section: Sea-salt Schemementioning
confidence: 99%
“…As one of the major components of primary aerosols, sea-salt aerosols contributes to 20 %-40 % of secondary inorganic aerosols (SIAs) over coastal regions Yang et al, 2016). These particles can provide surface areas for condensation and reaction of nitrogen and sulfur, making the simulated concentrations of SIAs more accurate (Kelly et al, 2010;Im, 2013).…”
Section: Sea-salt Schemementioning
confidence: 99%
“…Previously, we have demonstrated that using the AMF calculated with MAX-DOAS-measured NO 2 vertical profiles could remarkably improve the accuracy of retrievals of NO 2 column densities (VCDs) Xing et al, 2017). On top of that, due to complex terrain and weather conditions, uncertainties in emission inventories, and imperfect model parameterization, chemical transport models face difficulties in capturing the vertical structures of atmospheric composition on the TP (Yang et al, 2018b), the uncertainties of which could be constrained through the assimilation of observations from this dataset. Section 2 describes the observation site, MAX-DOAS instrument and retrieval algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2017). Tibetan Plateau generally showed the clean air quality due to the unique landform and scarce industrial activity (Yang et al, 2018). In addition, it was interesting to note that the Altai region and Taklimakan desert in Xinjiang autonomous region also showed some NO3hotspots, though these regions were often believed to be the remote region.…”
Section: Spatial Pattern Of New-developed No3datasetmentioning
confidence: 99%